Power storage device
The use of first and second particles with specific circularity and size ratios in the negative electrode active material layer addresses the balance of density and voids, enhancing the specific surface area and reducing stress, thus improving the cycle characteristics and capacity retention of lithium ion secondary batteries.
Patent Information
- Application Number
- JP2023095371
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2043-06-09
AI Technical Summary
Existing negative electrode active materials in lithium ion secondary batteries face challenges in achieving a balance between high packing density and maintaining appropriate voids to accommodate the expansion and contraction of silicon-based materials, leading to increased internal stress and reduced capacity retention.
A negative electrode active material layer comprising first particles with an average circularity of 0.5 to 0.9 and second particles with an average circularity greater than 0.9, where the second particles are smaller in size to fill gaps between the first particles, creating a more favorable specific surface area and void distribution, thereby reducing internal stress and maintaining capacity.
The configuration enhances the specific surface area and void distribution in the negative electrode layer, suppressing capacity loss and internal stress, resulting in improved cycle characteristics and capacity retention of the battery.
Smart Images

Figure 2024176647000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electricity storage device. [Background technology]
[0002] The negative electrode active material disclosed in JP 2017-92009 A includes negative electrode active material particles containing silicon compound particles including a silicon compound (SiOx: 0.5≦x≦1.6). The silicon compound particles contain at least one of Li2SiO3 and Li4SiO4. The negative electrode active material particles have a loose bulk density BD of 0.5 g / cm 3 More than 0.9g / cm 3 and the tapped bulk density TD is 0.7 g / cm 3 More than 1.2g / cm 3 The density is equal to or less than 100%, and the degree of compression defined by (TD-BD) / TD is equal to or less than 25%. The publication states that the negative electrode active material particles containing silicon compound particles have a SiO2 component portion that becomes unstable when lithium is inserted and removed from the silicon compound during charging and discharging of the battery, and that the irreversible capacity generated during charging can be reduced. The publication also states that the negative electrode active material particles satisfy a predetermined loose bulk density, tap density, and degree of compression, thereby improving the cycle characteristics of the battery. Furthermore, the publication also states that the use of such negative electrode active material particles can improve the electrode filling property, and thus the cycle characteristics of the secondary battery can be improved.
[0003] The negative electrode active material disclosed in JP 2019-175851 A contains composite particles in which at least a part of the surface of silicon oxide particles and graphite particles is coated with a low-crystalline carbon material having lower crystallinity than the graphite particles. The composite particles contain 50 to 500 parts by mass of silicon oxide particles and 200 to 2000 parts by mass of graphite particles with respect to 100 parts by mass of the low-crystalline carbon material. In the composite particles, two peaks of weight loss due to heating are observed in a differential curve of a thermogravimetric curve obtained by thermogravimetric analysis in an oxygen-containing atmosphere, and the peak observed on the lower temperature side of the two peaks is observed in a temperature range of 500 to 600 ° C. According to the publication, it is described that it is possible to provide a negative electrode active material for lithium ion secondary batteries that can be used to manufacture lithium ion secondary batteries having a large initial discharge capacity and excellent charge / discharge cycle characteristics. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-92009 A [Patent Document 2] JP 2019-175851 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present inventors wish to realize a more preferable specific surface area in a negative electrode active material layer containing silicon. [Means for solving the problem]
[0006] The electricity storage device disclosed herein includes a negative electrode active material layer containing a negative electrode active material. The negative electrode active material contains first particles and second particles containing silicon. The second particles are different from the first particles. The average circularity CR1 of the first particles is 0.5 or more and 0.9 or less. The average circularity CR2 of the second particles is greater than 0.9. The ratio (D2 / D1) of the average particle diameter D1 of the first particles to the average particle diameter D2 of the second particles is 0.1 or more and less than 1. With this configuration, a more preferable specific surface area can be achieved in the silicon-containing negative electrode active material layer in the electricity storage device. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view of an electricity storage device 100. As shown in FIG. [Diagram 2] FIG. 2 is a schematic diagram of the electrode body 20. [Diagram 3] FIG. 3 is a schematic cross-sectional view of the negative electrode sheet 60. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] An embodiment of the technology disclosed herein will be described below. The embodiment described herein is not intended to limit the technology disclosed herein. The technology disclosed herein is not limited to the embodiment described herein unless otherwise specified. The drawings are drawn typically and do not necessarily reflect the actual product. In addition, the same reference numerals are appropriately used for members and parts that perform the same function, and duplicated explanations are omitted. In addition, the notation "A to B" indicating a numerical range means "A or more and B or less" unless otherwise specified, and also includes the meaning of "greater than A and less than B."
[0009] In this specification, the term "electricity storage device" refers to a device in which charging and discharging occurs by the movement of charge carriers between a pair of electrodes (positive and negative electrodes) via an electrolyte. Such electricity storage devices include secondary batteries such as lithium ion secondary batteries, nickel-metal hydride batteries, and nickel-cadmium batteries; and capacitors such as lithium ion capacitors and electric double layer capacitors. In the following, an embodiment in which a lithium ion secondary battery is used as an example of the above-mentioned electricity storage device will be described.
[0010] Fig. 1 is a schematic cross-sectional view of an electricity storage device 100. Fig. 1 is a schematic cross-sectional view along the widest surface of the electricity storage device 100. As shown in Fig. 1, the electricity storage device 100 includes an electrode body 20, a case 30, and a non-aqueous electrolyte solution 80.
[0011] Fig. 2 is a schematic diagram of the electrode body 20. As shown in Fig. 1 and Fig. 2, the electrode body 20 is a wound electrode body in which a long sheet-like positive electrode sheet 50 and a long sheet-like negative electrode sheet 60 are overlapped with a long sheet-like separator 70 interposed therebetween and wound in the sheet longitudinal direction (hereinafter also simply referred to as the "longitudinal direction"). In the electrode body 20, an exposed region 52a in the positive electrode sheet 50 and an exposed region 62a in the negative electrode sheet 60 protrude outward from both ends in the short direction perpendicular to the longitudinal direction.
[0012] As shown in FIG. 1 and FIG. 2, the positive electrode sheet 50 includes a long sheet-like positive electrode collector foil 52 and a positive electrode active material layer 54. The positive electrode collector foil 52 is, for example, an aluminum foil. In this embodiment, the positive electrode collector foil 52 has a region where the positive electrode active material layer 54 is provided and an exposed region 52a where the positive electrode active material layer 54 is not provided and the surface of the positive electrode collector foil 52 is exposed. The positive electrode active material layer 54 is provided, for example, in a band shape along the longitudinal direction on one side or both sides (both sides here) of the positive electrode collector foil 52. The positive electrode active material layer 54 is not provided at the end in the short side direction (the end on the left side in the figure). Here, the exposed region 52a is a band-shaped region at the end in the short side direction (the end on the left side in the figure). As shown in FIG. 1, the current collector plate 42a is attached to the exposed region 52a.
[0013] The positive electrode active material layer 54 contains, for example, a positive electrode active material. The positive electrode active material is, for example, a lithium nickel cobalt manganese composite oxide (NCM) (for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi 0.5 Mn 1.5 Examples of the positive electrode active material layer 54 include lithium transition metal oxides such as LiFePO4, and lithium transition metal phosphate compounds such as LiFePO4. The positive electrode active material layer 54 may contain a conductive material, a binder, and the like in addition to the positive electrode active material. Examples of the conductive material include carbon black such as acetylene black (AB), and other carbon materials such as graphite. Examples of the binder include polyvinylidene fluoride (PVDF).
[0014] FIG. 3 is a schematic cross-sectional view of the negative electrode sheet 60. In FIG. 3, the cross-sectional structure of the negative electrode current collector foil 62 and the negative electrode active material layer 64 in the negative electrode sheet 60 is partially enlarged. As shown in FIGS. 1 to 3, the negative electrode sheet 60 includes a long sheet-like negative electrode current collector foil 62 and a negative electrode active material layer 64. The negative electrode current collector foil 62 is, for example, a copper foil. In this embodiment, the negative electrode current collector foil 62 has a region where the negative electrode active material layer 64 is provided and an exposed region 62a where the negative electrode active material layer 64 is not provided and the surface of the negative electrode active material layer 64 is exposed. The negative electrode active material layer 64 is provided in a strip shape along the longitudinal direction on one or both sides (both sides in this case) of the negative electrode current collector foil 62, for example. The negative electrode active material layer 64 is not provided on the end (the right end in the figure) in the short direction perpendicular to the longitudinal direction. The exposed area 62a is a strip-shaped area at the end in the short direction (the end on the right side in the drawing). As shown in Fig. 1, the current collector plate 44a is attached to the exposed area 62a.
[0015] By the way, for example, in order to increase the capacity of the electric storage device, a negative electrode active material containing silicon may be used. The inventors' study has revealed that, although the packing density of the negative electrode active material in the negative electrode active material layer can be increased by using only a negative electrode active material with a high average circularity, the negative electrode active material is likely to increase internal stress due to the lack of voids in the negative electrode active material. The inventors' study has revealed that, although the negative electrode active material layer is provided with an appropriate amount of voids by using only a negative electrode active material with a low average circularity, the negative electrode active material is likely to crack due to the stress of pressing the negative electrode active material layer in the manufacturing process. The cracking of the negative electrode active material increases the specific surface area in the negative electrode active material layer, which may cause a decrease in the capacity of the electric storage device. The inventors thought that, for example, by suppressing the increase in the specific surface area before and after pressing in the manufacturing process, a more preferable specific surface area can be realized in the negative electrode active material layer containing silicon. The inventors thought that this would suppress the decrease in the capacity of the electric storage device and realize a high-density negative electrode active material layer in which the internal stress due to expansion and contraction is appropriately alleviated. Here, the term "negative electrode active material with a high average circularity" refers to a negative electrode active material with an average circularity of greater than 0.9. The term "negative electrode active material with a low average circularity" refers to a negative electrode active material with an average circularity of 0.9 or less.
[0016] 3, the negative electrode active material layer 64 includes a negative electrode active material 68. Here, the negative electrode active material 68 includes first particles 681 and second particles 682. The first particles 681 are particles containing silicon. The second particles 682 are particles containing silicon and different from the first particles 681. The first particles 681 and the second particles 682 are different from each other in, for example, the average circularity and the average particle diameter.
[0017] The average circularity CR1 of the first particles 681 is, for example, 0.5 to 0.9. From the viewpoint of increasing the density of the negative electrode active material layer 64, the average circularity CR1 is preferably 0.6 or more, more preferably 0.7 or more, and even more preferably 0.75 or more. From the viewpoint of providing an appropriate gap in the negative electrode active material layer 64, the average circularity CR1 is preferably 0.85 or less, and more preferably 0.8 or less. The average circularity CR2 of the second particles 682 is, for example, greater than 0.9. From the viewpoint of increasing the density of the negative electrode active material layer 64, the average circularity CR2 is preferably 0.91 or more, more preferably 0.92 or more, and even more preferably 0.93 or more. From the viewpoint of providing an appropriate gap in the negative electrode active material layer 64, the average circularity CR2 is preferably less than 1, preferably 0.98 or less, more preferably 0.96 or less, and even more preferably 0.95 or less.
[0018] In this specification, the "average circularity" of a particle refers to the arithmetic mean value of the circularity of 1000 or more (e.g., 3000) particles randomly selected. The circularity here is determined by image analysis of the particle image, and calculating the circularity of the particle (L) and the circularity of a circle having the same projected area as the particle (L0) using the following formula (A): Circularity = L0 / L Formula (A) As the image analyzer used for calculating the average circularity, an image type particle size distribution measuring device used for this type of application can be used without any particular limitation.
[0019] The second particles 682 are preferably particles having a size smaller than that of the first particles 681. This allows the relatively small second particles 682 to enter the gaps between the relatively large first particles 681, thereby increasing the density of the negative electrode active material layer 64. From the viewpoint of realizing such an effect, the ratio (D2 / D1) of the average particle diameter D1 of the first particles 681 to the average particle diameter D2 of the second particles 682 is preferably 0.1 or more and less than 1, preferably 0.8 or less, and more preferably 0.6 or less. From the viewpoint of realizing the effect of suppressing the decrease in the capacity maintenance rate of the power storage device 100, the ratio (D2 / D1) is more preferably 0.5 or less, and particularly preferably 0.4 or less. In order to prevent the second particles 682 entering the gaps between the first particles 681 from excessively reducing the gaps of the negative electrode active material layer 64, the ratio (D2 / D1) is preferably 0.15 or more, and more preferably 0.2 or more.
[0020] The average particle diameter D1 and the average particle diameter D2 are not particularly limited as long as the effect of the technology disclosed herein can be realized. The average particle diameter D1 is preferably about 3 μm to 25 μm. From the viewpoint of providing an appropriate amount of voids in the negative electrode active material layer 64, the average particle diameter D1 is preferably 5 μm or more, more preferably 7.5 μm or more, or preferably 20 μm or less, and more preferably 15 μm or less. The average particle diameter D2 is preferably about 0.3 μm to 10 μm. From the viewpoint of making it easier for the second particles to enter the voids between the first particles 681, the average particle diameter D2 is preferably 8 μm or less, more preferably 6 μm or less, and from the viewpoint of realizing the effect of suppressing the decrease in the capacity maintenance rate, it is further preferably 5 μm or less, and particularly preferably 4 μm or less. In order to prevent the second particles 682 entering the gaps between the first particles 681 from excessively reducing the gaps in the negative electrode active material layer 64, the average particle diameter D2 is preferably 0.5 μm or more, and more preferably 0.7 μm or more. From the viewpoint of realizing the effect of suppressing a decrease in the capacity maintenance rate in addition to the above effect, the average particle diameter D2 is more preferably 1 μm or more, and particularly preferably 2 μm or more. In this specification, the term "average particle diameter" refers to the particle diameter (D 50 This refers to the particle size.
[0021] In order to provide an appropriate amount of voids, the negative electrode active material layer 64 preferably contains more first particles 681 than second particles 682. The ratio (mass ratio) (C2 / C1) of the content C1 of the first particles 681 to the content C2 of the second particles 682 in the negative electrode active material 68 is not particularly limited as long as the effect of the technique disclosed herein is realized. The ratio (C2 / C1) is preferably approximately 0.03 or more and less than 1. From the viewpoint of realizing the effect of the technique disclosed herein, the ratio (C2 / C1) is preferably 0.05 or more, more preferably 0.08 or more, and even more preferably 0.1 or more. In addition to such an effect, from the viewpoint of suppressing a decrease in the capacity maintenance rate of the power storage device 100, the ratio (C2 / C1) is preferably 0.8 or less, more preferably 0.7 or less, even more preferably 0.5 or less, and particularly preferably 0.3 or less.
[0022] The first particle 681 and the second particle 682 may both be composite particles of silicon and carbon, for example. The composite particles of silicon and carbon are, for example, particles in which silicon and carbon are integrated and behave like a single particle. Hereinafter, the composite particles of silicon and carbon are also referred to as "Si / C particles." When the first particle 681 and the second particle 682 are Si / C particles, the degree of deformation of the first particle 681 and the second particle 682 during the manufacturing process of the electricity storage device 100 and during charging and discharging can be reduced. Therefore, a suitable specific surface area is easily achieved in the negative electrode active material layer 64.
[0023] The Si / C particles contain silicon, for example, on the surface and inside of the carbon material. The carbon material may be, for example, a porous carbon material. Here, the porous carbon material refers to a carbon material having pores. The pores of the porous carbon material may contribute to, for example, mitigating the expansion and contraction of silicon accompanying the charging and discharging of the power storage device 100. For this reason, when the carbon material of the Si / C particles is a porous carbon material, the internal stress of the negative electrode active material layer 64 can be reduced. For example, the silicon may be supported in the pores of the porous carbon material. When the silicon is supported in the pores of the porous carbon material, for example, when the silicon expands, the pores can absorb the expansion. Although not particularly limited, the porous carbon material is preferably fibrous or granular.
[0024] The Si / C particles are manufactured, for example, by the method described below. However, the manufacturing method of the Si / C particles is not limited to the one described below. The manufacturing method of the Si / C particles includes, for example, a preparation step, a mixing step, and a heating step.
[0025] The preparation step is, for example, a step of preparing a composite of a porous carbon material and SiO (SiO-C composite) as a raw material, and a metal reducing agent. As the metal reducing agent, any metal reducing agent used for this type of application can be used without any particular limitation. The metal reducing agent may be, for example, magnesium (Mg), aluminum (Al), or the like.
[0026] The mixing step is, for example, a step of mixing the raw materials prepared in the preparation step. By carrying out the mixing step, a mixture of the raw materials, SiO-C composite and a metal reducing agent, is obtained. Here, the raw materials may be mixed by a conventionally known mixing means such as a mortar.
[0027] The heating step is, for example, a step of heating the mixture obtained in the mixing step. By carrying out the heating step, a reduction reaction by a metal reducing agent can occur. As a result, for example, SiO in the SiO-C composite is reduced to Si, and silicon (Si) is placed in the pores of the porous carbon material. The heating step is preferably carried out in an inert atmosphere, for example, a rare gas atmosphere such as an argon atmosphere, or a nitrogen atmosphere. The temperature condition of the heating step may be, for example, 200°C to 500°C. The heating time may be, for example, 0.1 hours to 10 hours.
[0028] When the first particle 681 and the second particle 682 are Si / C particles, for example, by appropriately adjusting the size of the SiO-C composite as a raw material, it is possible to realize the desired average particle diameters D1 and D2 for the first particle 681 and the second particle 682. By appropriately adjusting the amount of SiO in the SiO-C composite as a raw material, it is possible to adjust the amount of silicon (Si) contained in the first particle 681 and the second particle 682.
[0029] In the embodiment shown in FIG. 3, the negative electrode active material layer 64 further includes graphite particles 683. In addition to the first particles 681 and the second particles 682, the graphite particles 683 can also function as a negative electrode active material. In addition, the graphite particles 683 have a smaller degree of expansion and contraction accompanying charging and discharging of the electricity storage device 100 compared to the first particles 681 and the second particles 682 containing silicon. Therefore, by including the graphite particles 683 in the negative electrode active material layer 64, the graphite particles 683 can play a part of the role of the negative electrode active material in the negative electrode active material layer 64. This can better suppress the expansion and contraction of the negative electrode sheet 60 due to charging and discharging of the electricity storage device 100.
[0030] The graphite particles 683 may be, for example, artificial graphite, natural graphite, etc. The graphite particles 683 may have a coating layer of amorphous carbon on the surface. Although not particularly limited, the graphite particles 683 are, for example, substantially spherical. In this specification, the term "substantially spherical" with respect to the graphite particles 683 means that the average aspect ratio of the graphite particles 683 based on the observation with an electron microscope (SEM) is 1 to 2 (preferably 1 to 1.5). The average aspect ratio is obtained, for example, by obtaining a planar SEM observation image of the graphite particles 683, randomly selecting a plurality of graphite particles 683 (for example, 10 to 100) from the SEM observation image, calculating the aspect ratio of each, and calculating the arithmetic average value. The average particle diameter of the graphite particles 683 may be, for example, 5 μm to 30 μm, or may be 10 μm to 20 μm.
[0031] When the negative electrode active material contains graphite particles 683, from the viewpoint of realizing the above-mentioned effects, when the total of the first particles 681, the second particles 682, and the graphite particles 683 is taken as 100 mass%, the proportion of the graphite particles 683 is preferably approximately 20 mass% to 80 mass% (preferably 40 mass% to 75 mass%, and more preferably 50 mass% to 70 mass%).
[0032] The negative electrode active material layer 64 may contain a conductive material in addition to the negative electrode active material. As the conductive material, for example, carbon nanotubes such as single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), and multi-walled carbon nanotubes (MWCNT); carbon black such as acetylene black (AB); carbon fibers; and the like may be used. Among them, carbon nanotubes are preferable, and single-walled carbon nanotubes are more preferable. By using carbon nanotubes as the conductive material, the conductive path is more preferably maintained, and the cycle characteristics of the electricity storage device 100 may be further improved.
[0033] The proportion of the negative electrode active material when the entire negative electrode active material layer 64 is taken as 100 mass % is, for example, preferably 80 mass % or more, more preferably 90 mass % to 99 mass %, and may be 95 mass % to 99 mass %. The proportion of the conductive material when the entire negative electrode active material layer 64 is taken as 100 mass % may be, for example, 0.01 mass % to 1 mass %.
[0034] The negative electrode active material layer 64 may contain a binder in addition to the negative electrode active material. Examples of the binder include carboxymethyl cellulose (CMC), polyacrylic acid (PAA), styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), and the like. Among them, carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and styrene butadiene rubber (SBR) can be preferably used. The ratio of the binder when the entire negative electrode active material layer 64 is taken as 100% by mass may be, for example, 1% by mass to 10% by mass.
[0035] In producing the negative electrode sheet 60, the negative electrode active material and materials used as necessary (such as conductive materials and binders) are dispersed in an appropriate solvent (such as water) to prepare a paste (or slurry) composition. Next, this composition is applied to the surface of the negative electrode current collector foil 62 and dried. Then, by pressing as necessary, the negative electrode sheet 60 is produced in which the negative electrode active material layer 64 is provided on the surface of the negative electrode current collector foil 62.
[0036] The separator 70 may be, for example, a porous sheet (film) made of a resin material such as polyethylene (PE), polypropylene (PP), polyester, cellulose, or polyamide. The porous sheet may have a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). A heat-resistant layer (HRL) may be provided on the surface of the separator 70.
[0037] The case 30 is, for example, an outer container that houses the electrode body 20 and the non-aqueous electrolyte 80. Here, the case 30 is a flat rectangular case. As shown in FIG. 1, the case 30 has a positive electrode terminal 42, a negative electrode terminal 44, a safety valve 36, and a liquid injection hole (not shown). The positive electrode terminal 42 is, for example, a terminal for external connection on the positive electrode side. Here, the positive electrode terminal 42 is electrically connected to the positive electrode sheet 50 of the electrode body 20 via a current collector 42a. The negative electrode terminal 44 is, for example, a terminal for external connection on the negative electrode side. Here, the negative electrode terminal 44 is electrically connected to the negative electrode sheet 60 of the electrode body 20 via a current collector 44a. The safety valve 36 is, for example, a thin-walled portion that is set to release the internal pressure when the internal pressure of the case 30 rises to a predetermined level or higher. The liquid injection hole is, for example, a portion for injecting the non-aqueous electrolyte 80 into the case 30.
[0038] The non-aqueous electrolyte 80 contains, for example, an electrolyte salt, a non-aqueous solvent, and a scavenger. The electrolyte salt can be, for example, LiPF6. The concentration of the electrolyte salt in the non-aqueous electrolyte 80 may be, for example, 0.7 mol / L to 1.3 mol / L. The non-aqueous solvent may be, for example, a carbonate such as ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), or trifluorodimethyl carbonate (TFDMC). These may be used alone or in combination of two or more.
[0039] The power storage device 100 can be used for various purposes. Suitable applications include a driving power source mounted on vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs). The power storage device 100 can be used as a storage battery for small-sized power storage devices and the like. A plurality of power storage devices 100 may be connected in series and / or in parallel to form a battery pack.
[0040] As described above, the power storage device 100 includes the negative electrode active material layer 64 including the negative electrode active material 68. The negative electrode active material 68 includes first particles 681 including silicon, and second particles 682 including silicon and different from the first particles 681. Here, the average circularity CR1 of the first particles 681 is 0.5 or more and 0.9 or less. The average circularity CR2 of the second particles 682 is larger than 0.9. The ratio (D2 / D1) of the average particle diameter D1 of the first particles 681 to the average particle diameter D2 of the second particles 682 is 0.1 or more and less than 1.
[0041] In the electricity storage device 100 having such a configuration, the negative electrode active material 68 including the first particles 681 containing silicon and the second particles 682 containing silicon is used, thereby realizing a high capacity. The average particle diameter D1 of the first particles 681 having a relatively low average circularity is larger than the average particle diameter D2 of the second particles 682 having a relatively high average circularity. Therefore, the second particles 682 are likely to enter the gaps generated between the first particles 681 and the first particles 681. This makes it possible to suppress an increase in the specific surface area of the negative electrode active material layer 64 and realize a more preferable specific surface area. In addition to the effect of making the specific surface area of the negative electrode active material layer 64 more preferable, appropriate gaps can be maintained within the negative electrode active material layer 64. Therefore, even if the negative electrode active material 68 expands and contracts with the charging and discharging of the electricity storage device 100, the expansion and contraction of the negative electrode active material 68 is eliminated by the gaps. This makes it possible to suppress an increase in internal stress in the negative electrode active material layer 64 and a break in the conductive path.
[0042] Test examples relating to the present invention will be described below, but it is not intended that the present invention be limited to those shown in the following test examples.
[0043] <Preparation of test cell> Example 1 In the preparation of the negative electrode sheet, first, materials were prepared. As the negative electrode active material, first particles, second particles, and graphite particles were prepared. The first particles were Si / C particles having an average circularity of 0.64 and an average particle diameter of 10 μm. The second particles were Si / C particles having an average circularity of 0.95 and an average particle diameter of 2 μm. The graphite particles were graphite particles having an average particle diameter of 15 μm. As the conductive material, single-walled carbon nanotubes (SWCNT) were prepared. As the binder, carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and styrene butadiene rubber (SBR) were prepared. These were mixed with water as a solvent in a mass ratio of the first particles:second particles:graphite particles:SWCNT:CMC:PAA:SBR=31.5:3.5:65:0.1:1:1:1.5 to prepare a negative electrode mixture paste.
[0044] In the preparation of the negative electrode mixture paste, first, the first and second particles, the SWCNT paste (solid content rate 2%), and the dispersion medium were put into a kneader, and the first paste was prepared by dispersing and mixing at 3000 rpm using a disperser. Next, the graphite particles, CMC, and PAA were dry-mixed using a stirring granulator. Then, the first paste, the mixed powder obtained by dry mixing, and the dispersion medium (water) were kneaded and kneaded. The solid content rate during the kneading and kneading was 65%. SBR and the dispersion medium (water) were further added to the kneaded and kneaded mixture. In this way, the negative electrode mixture paste was prepared. The negative electrode mixture paste was applied in a strip shape on both sides of a copper foil having a thickness of 10 μm. Then, the paste on the copper foil was dried, pressed to a predetermined thickness, and then processed to a predetermined dimension to prepare a negative electrode sheet.
[0045] Next, lithium nickel cobalt manganese composite oxide (NCM) as a positive electrode active material, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVDF) as a binder were prepared. These were mixed with N-methylpyrrolidone (NMP) as a solvent so that the mass ratio of NCM:AB:PVDF was 100:1:1 to prepare a positive electrode composite paste. This paste was applied in a strip shape to both sides of an aluminum foil with a thickness of 15 μm. Then, the paste on the aluminum foil was dried, pressed to a predetermined thickness, and processed to a predetermined dimension to prepare a positive electrode sheet.
[0046] A current collecting lead was attached to each of the positive electrode sheet and the negative electrode sheet obtained as described above, and the sheets were laminated with a separator interposed therebetween to prepare a laminated electrode body. Next, the laminated electrode body was inserted into an exterior body made of an aluminum laminate sheet, a non-aqueous electrolyte was injected into the interior of the exterior body, and the opening of the exterior body was sealed to prepare a test cell of Example 1. As the separator, a porous polyolefin sheet having a three-layer structure of PP / PE / PP was used. As the non-aqueous electrolyte, a mixture of ethylene carbonate (EC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of EC:FEC:EMC:DMC=15:5:40:40, in which LiPF6 as a supporting salt was dissolved at a concentration of 1 mol / L was used.
[0047] The average circularity CR1 of the first particles and the average circularity CR2 of the second particles were calculated by image analysis of the particle images of the respective particles. In this image analysis, 3000 particles were used for the measurement. At this time, the circularity of each particle was calculated by the perimeter (L) of the particle, the perimeter (L0) of a circle having the same projected area as the particle, and the following formula (A): Circularity = L0 / L Formula (A) The average circularity CR1 and the average circularity CR2 were calculated by dividing the sum of the circularities of the 3,000 particles tested by the number of particles tested (3,000 in this example). In this test example, the average circularity CR1 and the average circularity CR2 were measured using an image-type particle size distribution measuring device.
[0048] Example 2 For the negative electrode active material, the first particles, the second particles, and the graphite particles were prepared in a mass ratio of the first particles: the second particles: the graphite particles = 26.25: 87: 25: 65. A test cell of this example was produced using the same materials and procedures as in Example 1 except for this.
[0049] Example 3 The second particles used had an average particle diameter D2 of 4 μm. Except for this, the test cell of this example was produced using the same materials and procedures as in Example 1.
[0050] Example 4 The second particles used had an average particle diameter D2 of 6 μm. Except for this, the test cell of this example was produced using the same materials and procedures as in Example 1.
[0051] --Example 5-- For the negative electrode active material, the first particles, the second particles, and the graphite particles were prepared in a mass ratio of the first particles:the second particles:the graphite particles=21:14:65. A test cell of this example was produced using the same materials and procedures as in Example 1 except for this.
[0052] -Comparative Example 1- The second particles used had an average particle diameter D2 of 0.7 μm. Except for this, the test cell of this example was produced using the same materials and procedures as in Example 1.
[0053] -Comparative Example 2- For the negative electrode active material, the first particles, the second particles, and the graphite particles were prepared in a mass ratio of the first particles: the second particles: the graphite particles = 35: 0: 65. A test cell of this example was produced using the same materials and procedures as in Example 1 except for this.
[0054] --Comparative Example 3-- For the negative electrode active material, the first particles, the second particles, and the graphite particles were prepared in a mass ratio of the first particles:the second particles:the graphite particles=0:35:65. A test cell of this example was produced using the same materials and procedures as in Example 1 except for this.
[0055] <Evaluation of specific surface area increase rate> For each test cell, the specific surface area of the negative electrode sheet before and after pressing in the above-mentioned production process was calculated to obtain the specific surface area increase rate. Here, the negative electrode sheet was cut to a specified size before and after pressing to obtain samples, and the amount of gas adsorption was measured by gas adsorption method using a commercially available specific surface area and pore distribution measuring device. Nitrogen was used as the adsorbed gas. The value obtained by the BET method was used for the specific surface area. Then, the following mathematical formula (B): Specific surface area increase rate (%) = [{(specific surface area after pressing) - (specific surface area before pressing)} / (specific surface area before pressing)] × 100 Formula (B) The specific surface area increase rate (%) was calculated using the above formula. The results are shown in the corresponding columns in Table 1.
[0056] <Evaluation of capacity retention rate> A cycle test was carried out on each test cell in an environment of 25°C, in which one cycle was CCCV charging (0.4C rate up to 4.2V, then cut off at 0.1C) followed by CC discharging (0.4C rate cut off at 2.5V) until 200 cycles were reached. The discharge capacity (initial capacity) at the first cycle and the discharge capacity at the 200th cycle were measured, and the following formula (C): Capacity retention rate (%) = (200th cycle discharge capacity / initial capacity) × 100 Formula (C) The capacity retention rate (%) of the test cell of each example was measured based on the above. The results are shown in the corresponding column in Table 1.
[0057] [Table 1]
[0058] As shown in Table 1, the test cells of Examples 1 to 5 contain the first particles and the second particles containing silicon as the negative electrode active material. In the test cells of Examples 1 to 5, the average circularity CR1 of the first particles is 0.5 or more and 0.9 or less, the average circularity CR2 of the second particles is greater than 0.9, and the ratio (D2 / D1) of the average particle diameter D1 of the first particles to the average particle diameter D2 of the second particles is 0.1 or more and less than 1. It was shown that the negative electrode sheets used in the test cells of Examples 1 to 5 have a lower specific surface area increase rate before and after pressing than the comparative example. It was found that the negative electrode sheets used in the test cells of Examples 1 to 5 are less susceptible to the effects of pressing than the negative electrode sheets of Comparative Examples 1 to 3, and a more preferable specific surface area was realized.
[0059] As described above, specific aspects of the technology disclosed herein include those described in the following sections. Section 1: An electricity storage device including a negative electrode active material layer containing a negative electrode active material, The negative electrode active material is a first particle comprising silicon; second particles different from the first particles, the second particles including silicon; Contains Where: The average circularity CR1 of the first particles is 0.5 or more and 0.9 or less, The average circularity CR2 of the second particles is greater than 0.9; a ratio (D2 / D1) of an average particle diameter D1 of the first particles to an average particle diameter D2 of the second particles is 0.1 or more and less than 1; Energy storage device. Section 2: Item 2. The power storage device according to item 1, wherein a ratio (C2 / C1) of a content C1 of the first particles to a content C2 of the second particles in the negative electrode active material is 0.5 or less. Section 3: 3. The electricity storage device according to item 1 or 2, wherein a ratio (D2 / D1) of the average particle diameter D1 to the average particle diameter D2 of the second particles is 0.5 or less. Section 4: 4. The electricity storage device according to any one of items 1 to 3, wherein the average particle diameter D2 is 1 μm or more and 5 μm or less. Section 5: 5. The electricity storage device according to any one of items 1 to 4, wherein the first particles and the second particles are both composite particles of silicon and carbon. Item 6: 6. The electricity storage device according to any one of items 1 to 5, wherein the negative electrode active material layer further contains graphite particles.
[0060] Although the embodiment of the technology disclosed herein has been described above, it is not intended that the technology disclosed herein be limited to the above embodiment. The technology disclosed herein may be implemented in other embodiments. The technology described in the claims includes various modifications and changes to the above-exemplified embodiments. For example, it is possible to replace a part of the above-described embodiment with another modified embodiment, and it is also possible to add another modified embodiment to the above-described embodiment. Furthermore, if a technical feature is not described as essential, it is also possible to delete it as appropriate. [Explanation of symbols]
[0061] 20 Electrode body 30 cases 50 Positive electrode sheet 60 Negative electrode sheet 62 Negative electrode current collector foil 64 Negative electrode active material layer 68 Negative electrode active material 681 1st particle 682 2nd particle 683 Graphite particles 100 Energy storage device
Claims
1. An electricity storage device including a negative electrode active material layer containing a negative electrode active material, The negative electrode active material is a first particle comprising silicon; second particles different from the first particles, the second particles including silicon; Contains Where: The average circularity CR1 of the first particles is 0.5 or more and 0.9 or less, The average circularity CR2 of the second particles is greater than 0.9; The ratio (D2 / D1) of the average particle diameter D1 of the first particles to the average particle diameter D2 of the second particles is 0.1 or more and less than 1. Energy storage device.
2. The power storage device according to claim 1 , wherein a ratio (C2 / C1) of a content C1 of the first particles to a content C2 of the second particles in the negative electrode active material is 0.5 or less.
3. The power storage device according to claim 2 , wherein a ratio (D2 / D1) of the average particle diameter D1 to the average particle diameter D2 of the second particles is 0.5 or less.
4. The power storage device according to claim 1 , wherein the average particle diameter D2 is 1 μm or more and 5 μm or less.
5. The power storage device according to claim 1 , wherein the first particles and the second particles are both composite particles of silicon and carbon.
6. The power storage device according to any one of claims 1 to 5, wherein the negative electrode active material layer further contains graphite particles.
Citation Information
Patent Citations
Lithium-ion secondary battery negative electrode material, production method for lithium-ion secondary battery negative electrode material, lithium-ion secondary battery negative electrode, and lithium-ion secondary battery
WO2019220576A1
Negative electrode for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery
WO2022176650A1
Secondary battery
WO2023053947A1
Lithium secondary battery with improved safety
WO2024019460A1
Negative electrode active substance, mixed negative electrode active substance material, negative electrode for nonaqueous electrolyte secondary battery, lithium ion secondary battery, negative electrode active substance manufacturing method, and lithium ion secondary battery manufacturing method
JP2017092009A
